El léxico eslovaco y su evolución: panorámica general (II) - Alvarado, Salustio (Eslavística Complutense, 2003)
Although its basis is fundamentally Slavonic, the Slovak vocabulary consists, to a greater or lesser degree, of elements of different origins. This article presents some general ideas about its incorporation into the language. The problem of bohemianisms is particularly thomy. Since etymological studies of Slovak are not very abundant, especially concerning Eastem languages, and considering no etymological dictionary of Slovak has so far been published, this essay, initially devised for students who have optionally chosen “History of the Slovak Language”, can be a modest contribution in this field. The first part of this paper was published in the former issue.